If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(c + 2) + -11 = 5(2c + 3) + -2 Reorder the terms: 9(2 + c) + -11 = 5(2c + 3) + -2 (2 * 9 + c * 9) + -11 = 5(2c + 3) + -2 (18 + 9c) + -11 = 5(2c + 3) + -2 Reorder the terms: 18 + -11 + 9c = 5(2c + 3) + -2 Combine like terms: 18 + -11 = 7 7 + 9c = 5(2c + 3) + -2 Reorder the terms: 7 + 9c = 5(3 + 2c) + -2 7 + 9c = (3 * 5 + 2c * 5) + -2 7 + 9c = (15 + 10c) + -2 Reorder the terms: 7 + 9c = 15 + -2 + 10c Combine like terms: 15 + -2 = 13 7 + 9c = 13 + 10c Solving 7 + 9c = 13 + 10c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-10c' to each side of the equation. 7 + 9c + -10c = 13 + 10c + -10c Combine like terms: 9c + -10c = -1c 7 + -1c = 13 + 10c + -10c Combine like terms: 10c + -10c = 0 7 + -1c = 13 + 0 7 + -1c = 13 Add '-7' to each side of the equation. 7 + -7 + -1c = 13 + -7 Combine like terms: 7 + -7 = 0 0 + -1c = 13 + -7 -1c = 13 + -7 Combine like terms: 13 + -7 = 6 -1c = 6 Divide each side by '-1'. c = -6 Simplifying c = -6
| 3/8x=120 | | y-6=4(x-3)+2 | | -7+x=x/10-6 | | x/3.1=6 | | 15y^2=4-7y | | 8+27w=72w | | (x+4/3)(x-7/3) | | 6d+4d+3= | | 8+27w= | | 2x+7=x+25 | | -7+x=34+2x | | 2/7z=6 | | 13t-(5-2t)=5(3t-1) | | 13x+39=65 | | c/4+7+2 | | 3x+-16=-1 | | 252-4x=41x+17 | | 4/3m=12 | | y=-5x^2-11 | | 9z-18=27 | | 3y=y+2+1 | | 11x=16x | | 7.7/76.23 | | 11=16x | | 3y=y+1+1 | | Y=-2/5x-1 | | 3x-6=-9x+25 | | (k/(4k^2-1))+(2/(4k^2+8k+3)) | | 2/3m=6 | | 7-7x=167-442x | | 13x^2+26x=39 | | 6y-4=44 |